Integrasi Nilai-Nilai Keislaman Pada Peserta Didik Melalui Pembelajaran Pendidikan Agama Islam - Dahirin; Rusmin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This study focuses on integrating Islamic Values among Students through Islamic Education Learning. The research method employed is literature review (library research), involving the analysis of conceptual information as well as qualitative and quantitative data from previously published scholarly articles. The role of the researcher is crucial in analyzing the discussed subject matter. Based on the results and discussions concerning the integration of Islamic values in Islamic Education learning, several main objectives are sought. These include strengthening students' understanding of Islamic teachings and their application in daily life and fostering character development based on Islamic values such as honesty, discipline, responsibility, and social care. Additionally, the integration aims to enhance students' spiritual and moral capabilities to practice Islamic teachings effectively. It encourages them to apply Islamic values in various aspects of life including school, family, and society. Educational institutions need effective strategies to ensure the robust integration of Islamic values among students and address challenges that may arise during this process.